SISTEM INFORMASI PENGGAJIAN PENGAJAR STUDI KASUS MABIT NURUL FIKRI - Anggi Fergian Pratama (2020)
As an educational organization, Mabit Nurul Fikri needs efficient and effective administrative management. Eventhough the current administrative management had been running well, their data are not yet integrated each other, for example teacher data and presence data. Therefore, management information systems is needed to help managing the administration process, so Mabit Nurul Fikri can increase their business activity. The purpose of this research is to develop an teacher payroll information systems. The author used the waterfall as system development method. The author is also using the UML diagram for modeling the system since this diagram is used as an object-oriented programming framework thinking. This research is using a PIECES framework to analyze the problem in current system. This payroll system is develop using Codeigniter, Angular, and MySql. There are two kind of user that defined in this system, treasurer and head of department. Treasurer has access to all the use case while the head of departement just has some of them. The result of this research is an internal dashboard which allow Mabit Nurul Fikri to store the teacher data, presence, and salary, to calculate the teacher salary, and to download the teacher salary document in PDF format.